Wind Riders Search for the scarlet macaws - Marlin , Jen; Burton, Izzy (New York, USA HarperCollins, 2022)
Hop aboard Wind Rider, a magical sailboat, with Max and Sofia, two kids trying to save the environment one problem at a time. Their second mission Protecting majestic scarlet macaw chicks in the most biodiverse place on Earth, the Amazon rain forest. Wind Riders is the perfect STEM chapter book series
English stories
Keywords: Children's stories